The Link between the Implementation of Management Functions on the Performance Primary Health Care Employees: Keterkaitan Penerapan Fungsi Manajemen Terhadap Kinerja Pegawai Puskesmas - Marlina Yusnita Nasution; Rapotan Hasibuan (Universitas Widya Gama Mahakam Samarinda, 2022)
Background: The condition of the management function (POAC) is one of the causes of declining employee performance in service organizations. Therefore, it is necessary to pay attention to the management function (POAC) in order to have a positive impact such as increasing employee performance at the Public health center Objectives: This study aims to determine the relationship between the management function (POAC) and employee performance at the Langga Payung Health Center.Research Metodes: The type of research used is quantitative with a cross sectional study design with a sample of 95 respondents. Data was collected by filling out a questionnaire. Data analysis was univariate and bivariate (chi square). Findings: The results showed that in general the management function (POAC) was categorized as good and the employee performance was classified as good. Meanwhile, the bivariate test proved the significance of the relationship only on the controlling function (p=0.008). Conclusion: There is no significant relationship between planning, organizing and actuating management functions with the performance of Langga Payung Health Center employees. And there is a significant relationship between the controlling management function and the performance of the Langga Payung Health Center employees. This means that respondents cannot prove that the Planning, Organizing and Actuating variables have a relationship with employee performance in this study and does not rule out other variables that can affect employee performance other than the management function at the Langga Payung Health Center.